Thinking with Bruno Latour: Toward a Renovated Sociology of Religion - Piraino, Francesco (Implicit religion, 2023)
This article discusses how Bruno Latour's sociology of associations can help renovate the sociology of religion and its subfields of spirituality, mysticism, and esotericism. It proposes a moratorium on the idea of modernity and its relative theories on secularisation, spiritualisation, and commodification, arguing for a renovated focus on ethnographical fieldwork. Drawing on Latour, this article suggests seeing the sociology of religion as including metaphysics, which has often been forgotten through a focus on power struggles. It suggests that the methodology of religious discourses could be crucial, avoiding descriptivism and hyper-specialisation and offering a tool that can be applied to different religious and cultural contexts. Furthermore, this article suggests that artistic products in popular culture are not only receptacles of social forces but could be seen as nonhuman actors, capable of producing new religious doctrines and practices. To conclude, this article discusses the ethical and political implications of Latour's sociology of associations, showing how its bottom- up approach favours a postcolonial approach to subjectivities and commensurability.